A new method to enhance organic photodetectors active layer trap doping by blending doping. (6th January 2020) - An, Tao; Liu, Xinying; Ma, Jianping
Abstract: In order to solve the problem of high concentration trap doping in the active layer of organic detector, a blending doping method is proposed in this paper. The influence of the doping concentration of C60 :C70 on the trap concentration in the P3HT:PC61 BM active layer and the optoelectronic performance of the detector are studied through experiments. It founds that the maximum doping concentration and trap concentration of active layer could arrive to 1.5 wt% and 3.26 × 10 18 cm −3 respectively after blending doping, which increased by 50% and one order of magnitude compared with the maximum doping concentration of single C60 (doping concentration:1.0 wt%, trap concentration: 5.83 × 10 17 cm −3 ), and the external quantum efficiency is increased by 8 folds from 1067.48% to 8510.17%. The result shows that the doping concentration and the trap concentration can be greatly improved using the blending doping method, and thereby the high concentration trap doping of the active layer can be achieved.